Calculation the optical energy band gap of LR115 SSNTD irradiated by α particle - Jaber Al-Tai,i, Hassan M. (Iraqi Journal of Physics, 2019)
The effect of α-particle irradiation on the optical absorption in nuclear track detectors (LR115) has been studied. These detectors have been irradiated with different doses. The optical absorption has been measured using the ultraviolet-visible (UV-1100) spectroscopy, that irradiation results in shifting the peaks of the optical absorption. The values of Urbach energy have been calculated from the position of steady-state optical band gap energy, for a standard sample which was unirradiated with indirect influence, has been found 1.9 eV whereas its value after irradiation 1.98 eV. In case of the direct influence, it is found to be, respectively, before irradiation 1.98 eV and after irradiation 2.05 eV. From these results, we can reveal that the values of energy gaps in direct–coincidence before and after irradiation greater than those for indirect one. The number of carbon atoms has been determined in each case for the optical energy gaps.